STUDY OF THE CONTAMINATING MICROBIOTA OF OLD PAPER SUPPORTS - Simona Isabela Dunca; Catalin Tanase; Claudia Padurariu; Tiberius Balaes; Elena Ardelean; Nicoleta Melniciuc Puica (European Scientific Journal, ESJ, 2014)
Biodeterioration has drawn the attention of different specialists who started to cooperate and to understand the need of joint research to have a picture as comprehensive as possible of the degradation agents and the measures that can be taken to salvage the heritage assets. This paper contains a description of the microbiota identified in two types of old paper supports part of a private collection from North Moldavia (Romania), namely a church book from the end of the 19th century for which the paper was obtained manually from textile fibres, and a book from 1870 with paper from cellulose pulp derived from wood. To the purpose of identifying the types of bacteria and fungi present on the supports examined, several comments were made related to the morphology of the colonies developed on the growth medium, which provided important indications for the determination based on the microscopical examination as well. Bacterial contamination (of the genera Bacillus, Clostridium, Pseudomonas and Micrococcus) was detected in most samples collected. The diversity of the fungi isolated from the paper supports (the genera Penicillium, Alternaria) is the result of the fact that since they are highly hygroscopic materials, they have the capability to retain water more easily, which stimulates fungal growth. The investigations made to determine the presence of microorganisms responsible for degradation and their identification allowed the discovery and acertainment of the real and justified need to find ways to prevent biodeterioration or to inactivate and destroy biodeteriogens by non-invasive, eco-friendly chemical and physical treatments.